Synthesis and In Vitro Evaluation of C-methylcalix[4]resorcinaryl octacinnamate and C-methylcalix[4]resorcinaryl octabenzoate as the Sunscreen - Budiana I Gusti M. Ngurah; Jumina Jumina; Chairil Anwar; Sunardi Sunardi; Mustofa Mustofa (Universitas Gadjah Mada, 2017)
The present study was aimed to synthesize and evaluate sunscreen activity of C-methylcalix[4]resorcinaryl octacinnamate and C-methylcalix[4]resorcinaryl octabenzoate. The target compounds were synthesized in 2 steps. They were a synthesis of C-methylcalix[4]-resorcinarene via acid catalyzed the condensation of resorcinol and acetaldehyde by using HCl catalyst, followed by esterification using cinnamoyl chloride and benzoyl chloride. The characterization of the target compounds was performed by IR, 1H-NMR, 13C-NMR, and LC-MS spectrometers. The sunscreen activity test was conducted by spectroscopic method and MTT-assay. Commercial sunscreen p-amino benzoic acid (PABA) was used as a comparator to the MTT assay. The sunscreen activity test used spectroscopic showed that C-methylcalix[4]resorcinaryl octacinnamate and C-methylcalix[4]resorcinaryl octabenzoate can absorb the ultraviolet radiation between 280 and 320 nm (UV-B) with the maximum absorption at 290 nm (ε = 31.535 M-1 cm-1) and 282 nm (ε = 42.217 M-1 cm-1), respectively. The results of MTT-assay indicated that the IC50 of C-methylcalix[4]resorcinaryl octacinnamate, C-methylcalix[4]resorcinaryl octabenzoate and PABA are 12.006, 20.568 and 12.564 ppm, respectively, it means that the order of sunscreen activity is C-methylcalix-[4]resorcinaryl octacinnamate, PABA and C-methylcalix[4]resorcinaryl octabenzoate.